Research of effective ways to use whey in meat product technologies - Chernyushok, Olga; Kushnir, Anatoly; Kondratyuk, Vladyslav; Polos, Denys; Cherniushok, Lora (My University, 2024)
One of the main tasks facing manufacturers of new products is to provide the population with products that have high consumer qualities and possess a set of the above-mentioned beneficial properties.

Одне з головних завдань, яке стоїть перед виробниками нових видів продукції, — це забезпечення населення продукцією, яка має високі споживчі якості та володіє набором зазначених корисних властивостей.
Keywords: кафедра технології м’яса і м’ясних продуктів; м’ясні продукти; варена ковбаса; м'ясо птиці; сироватка молочна